SAWOJAJAR WATERPARK DALAM PERUMNAS NEGERI KHAYAL - Antonius Bayu Kartiko; Kun Aniroh (Universitas Merdeka Malang, 2016)
Malang has biggest property icon in Southeast Asia that is Sawojajar. It makes Sawojajar possible to establish a tourism place and facilities at once for the regency residents. Sawojajar Waterpark will grow rapidly because it can be seen from Sawojajar residents needs and all Malang residents. The expect stakeholders can help the implementation of Sawojajar Waterpark establishment program are PDAM Malang, private investors, Sawojajar residents, Malang Tourism Agency, Malang Revenue Agency and Education Agency which active in tourism in Malang. The steps to achieve Sawojajar Waterpark in Perumnas Negeri Khayal can be reached in five steps, they are, land purchase, establishment with water installation, safety test from the vehicle that will establish, employees recruitment, promotion, and operational.